2019
DOI: 10.1542/peds.2018-3537
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes of Preterm Infants With Retinopathy of Prematurity by Treatment

Abstract: OBJECTIVE: Among extremely preterm infants, we evaluated whether bevacizumab therapy compared with surgery for retinopathy of prematurity (ROP) is associated with adverse outcomes in early childhood. METHODS: This study was a retrospective analysis of prospectively collected data on preterm (22-26 1 6/7 weeks' gestational age) infants admitted to the Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network centers who received bevacizumab or surgery exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 35 publications
1
87
0
1
Order By: Relevance
“…Two studies 10,12 have found worse outcomes in infants treated with IVB. For instance, Morin et al 10 and Natarajan et al 12 found an increase in death or adverse ND outcome in infants treated with bevacizumab by 2 years of corrected age. These studies included infants who were diagnosed and treated at multiple and various medical centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies 10,12 have found worse outcomes in infants treated with IVB. For instance, Morin et al 10 and Natarajan et al 12 found an increase in death or adverse ND outcome in infants treated with bevacizumab by 2 years of corrected age. These studies included infants who were diagnosed and treated at multiple and various medical centers.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that IVB can seep into the systemic circulation and may potentially affect brain development of the preterm infant is concerning. 7,8 Several retrospective studies [9][10][11][12][13] have assessed the risk of neurodevelopmental impairment (NDI) related to IVB therapy in preterm infants but reported conflicting results. In addition, the population of periviable infants who are at highest risk for posteriorly located ROP disease, and who could be the most vulnerable subjects for the adverse effects of anti-VEGF therapy, was adequately represented in only one study that showed higher death and developmental impairment in the bevacizumab-treated group.…”
mentioning
confidence: 99%
“…These animal findings were substantiated in humans when use of Avastin, a humanized anti-VEGF monoclonal antibody that had proven effective for pathological retinal neovascularization in adults, was first shown to be efficacious in treatment of ROP [35][36][37]. However, there is concern for potential adverse local and systemic effects of intraocular anti-VEGF treatments [38][39][40][41][42][43]. VEGF is now recognized as an important trophic factor for a variety of retinal cell types including retinal neurons, RPE, and glia [44,45].…”
Section: Anti-vegf Treatment For Ropmentioning
confidence: 93%
“…Or, le VEGF est indispensable au développement cérébral, rénal et pulmonaire. Des inquiétudes se sont faites jour à la suite de la publication d'études épidémiologiques montrant une association entre traitement par anticorps anti-VEGF et anomalies neuro-développementales à long terme [45]. Ces données restent toutefois à confirmer [46].…”
Section: Synthèse Revuesunclassified